Arsenic Trioxide During Consolidation for Patients with Previously Untreated Low/Intermediate Risk Acute Promyelocytic Leukaemia May Eliminate the Need for Maintenance Therapy - Coutre, Steven E. (2014)
A total of 105 patients (age ≥ 18 years) with newly diagnosed low or intermediate risk acute promyelocytic leukaemia (APL) were treated with a standard induction and consolidation regimen including arsenic trioxide (ATO). Sixty-eight patients who were polymerase chain reaction (PCR) negative for PML-RARA post-consolidation were randomized to either one year of maintenance with tretinoin, mercaptopurine and methotrexate, or observation. Enrollment in this non-inferiority trial was stopped prematurely due to slow accrual. With a median follow up of 36.1 months, the overall survival of the 105 patients was 93%, and there have been no relapses in the patients randomized to maintenance or observation. These results demonstrate that cures can be expected in >90% of patients with low and intermediate risk APL and suggest that maintenance therapy may not be needed if patients are treated with an intensive post-remission regimen including ATO. This trial was registered at clinicaltrials.gov as #NCT00492856.